Design, fabrication and demonstration of a 1x20 multimode interference splitter for parallel biosensing applications - Najeeb, Najla; Zhang, Yaping; Mellor, Christopher J.; Benson, Trevor M. (IOP Publishing, 2016)
This paper presents the experimental achievement of a silicon-on-insulator 1x20 MMI splitter andsimulation evaluations of the TE-like and TM-like mode MMI splitters for parallel biosensing applications. Device fabrication technology and optical characterisation results are provided.